2011
DOI: 10.1097/icu.0b013e3283499420
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and management of vision loss following orbital and facial trauma

Abstract: Conservative management is the first line treatment for TON. The evidence strongly supports lateral canthotomy and inferior cantholysis as best treatment for RBH. There is no consensus as to whether enucleation or evisceration is the best treatment for irretrievable devastating globe injury. The choice of management is currently determined by surgeon preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 55 publications
1
48
0
6
Order By: Relevance
“…Although the current trend leans toward evisceration because of the rarity of sympathetic ophthalmia and better cosmetic outcome compared with enucleation, the preference of these procedures is still controversial. 3,4 Savar et al 5 reported 51 and 5 enucleation and evisceration cases among 660 traumatized eyes, respectively. In contrast, Toit et al 6 reported primary enucleation in 3 eyes and evisceration in 491 eyes, respectively.…”
Section: Referencesmentioning
confidence: 99%
“…Although the current trend leans toward evisceration because of the rarity of sympathetic ophthalmia and better cosmetic outcome compared with enucleation, the preference of these procedures is still controversial. 3,4 Savar et al 5 reported 51 and 5 enucleation and evisceration cases among 660 traumatized eyes, respectively. In contrast, Toit et al 6 reported primary enucleation in 3 eyes and evisceration in 491 eyes, respectively.…”
Section: Referencesmentioning
confidence: 99%
“…Traumatic optic neuropathy can be primary or secondary [8]. The primary TON occurs in overtraction, rupture, contusion, and distortion of the optic nerve.…”
Section: Discussionmentioning
confidence: 97%
“…TON tedavisinde yüksek doz steroid, orbita dekompresyonu ya da konservatif tedavinin birbirine üstünlüğü açısından görüş birliği yoktur. [12] The International Optic Nerve Trauma Study çalışmasında yüksek doz steroid tedavisi ile orbita dekompresyon cerrahisi arasında ve bir başka çalışmada yüksek doz steroid tedavisi ve plasebo arasında görsel sonuç açısından istatistiksel olarak fark saptanmamıştır. [13,14] Olgunun travmadan bir ay sonra başvurması ve total görme kaybı olması nedeniyle TON açısından konservatif tedavi yoluna gidildi.…”
Section: Discussionunclassified